Empathy and assertiveness of nurses providing care to patients with psychological and somatic disorders - Motyka, Helena; Motyka, Katarzyna (Nursing in the 21st Century, 2015)
EMPATHY AND ASSERTIVENESS OF NURSES PROVIDING CARE TO PATIENTS WITH PSYCHOLOGICAL AND SOMATIC DISORDERSIntroduction. It seems that providing care to mentally ill patients requires more developed interpersonal skills than helping patients without mental disorders. Therefore, one might expect that psychiatric nurses would be more empathic and assertive than their colleagues from other wards.Aim. The aim of the study was to assess empathy and assertiveness levels of nurses working with patients with mental and without mental disorders.Material and methods. The study covered 120 nurses including 60 psychiatric nurses and 60 nurses from other wars. Empathy levels were measured using Davis’ IRI test, whereas assertiveness was determined using the Assertiveness Map developed by M. Król-Fijewska.Results. No differences were found between empathy and assertiveness levels of nurses working on psychiatric and non-psychiatric wards. A positive and statistically significant correlation (p=0.01) was discovered between the nurses’ age and their ability to adopt the other person’s point of view.Conclusion. Nurses’ empathy and assertiveness is unrelated to the type of ward they work on. Cognitive empathy of nurses increases with age – especially their ability to look at things the way patients do. Quality of nursing care could be improved by teaching nurses about communicating with patients. Such training sessions could be especially aimed at inexperienced nurses.